2020
DOI: 10.1177/1747493020969367
|View full text |Cite
|
Sign up to set email alerts
|

Addressing inactivity after stroke: The Collaborative Rehabilitation in Acute Stroke (CREATE) study

Abstract: Background Stroke patients are often inactive outside of structured therapy sessions – an enduring international challenge despite large scale organizational changes, national guidelines and performance targets. We examined whether experienced-based co-design (EBCD) – an improvement methodology – could address inactivity in stroke units. Aims To evaluate the feasibility and impact of patients, carers, and staff co-designing and implementing improvements to increase supervised and independent therapeutic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(61 citation statements)
references
References 18 publications
1
60
0
Order By: Relevance
“…Behavioural mapping data post implementation of codesigned changes, also confirmed the changes we saw in the space and environment of the units, with an increase in cognitive and social activity ( Jones et al, 2020 ). Additionally we found that stroke unit staff communicated more consistently about activity opportunities through leaflets and posters, highlighting activities available outside of structured therapy provision for example at weekends and evenings ( Jones et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…Behavioural mapping data post implementation of codesigned changes, also confirmed the changes we saw in the space and environment of the units, with an increase in cognitive and social activity ( Jones et al, 2020 ). Additionally we found that stroke unit staff communicated more consistently about activity opportunities through leaflets and posters, highlighting activities available outside of structured therapy provision for example at weekends and evenings ( Jones et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“… 46 Evidenced-based codesign and accelerated evidenced-based codesign was implemented in one study to address inactivity in stroke units. 44 …”
Section: Resultsmentioning
confidence: 99%
“…In rehabilitation, patients commonly experience boredom and lack autonomy 29. The challenge of creating more active rehabilitation environments has led to several groups exploring new models like environmental enrichment30–32 and programme redesign to increase autonomy and engagement,33 with varying degrees of success 33…”
Section: Continuing Specialist Inpatient Rehabilitationmentioning
confidence: 99%
“…32 In rehabilitation, patients commonly experience boredom and lack autonomy. 33 The challenge of creating more active rehabilitation environments has seen a number of groups explore new models like environmental enrichment 34,35,36 and program redesign to increase autonomy and engagement, 37 with varying degrees of success. 37 Identifying effective strategies to meet best practice rehabilitation guidelines, including standardised screening and higher-intensity training is a priority to optimise stroke rehabilitation and will require a fundamental shift in current approaches.…”
Section: Specialised Neurorehabilitation Servicesmentioning
confidence: 99%